Phase Space Insights: Wigner Functions for Qubits and Beyond - Sánchez-Soto, Luis L.; Muñoz, Ariana; de la Hoz, Pablo; Klimov, Andrei B.; Leuchs, Gerd (Applied Sciences, 2025)
Phase space methods, particularly Wigner functions, provide intuitive tools for representing and analyzing quantum states. We focus on systems with SU(2) dynamical symmetry, which naturally describes spin and a wide range of two-mode quantum models. We present a unified phase space framework tailored to these systems, highlighting its broad applicability in quantum optics, metrology, and information. After reviewing the core SU(2) phase-space formalism, we apply it to states designed for optimal quantum sensing, where their nonclassical features are clearly revealed in the Wigner representation. We then extend the approach to systems with an indefinite number of excitations, introducing a generalized framework that captures correlations across multiple SU(2)-invariant subspaces. These results offer practical tools for understanding both theoretical and experimental developments in quantum science.
CRIS-Team Scopus Importer:2025-05-23
Keywords: phase space; quantum information; Wigner functions